2013
DOI: 10.2463/mrms.2012-0044
|View full text |Cite
|
Sign up to set email alerts
|

Ring-shaped Lateral Ventricular Nodules Detected with Brain MR Imaging

Abstract: Purpose: We evaluated the prevalence and imaging characteristics of ring-shaped lateral ventricular nodules (RSLVNs) detected by postcontrast brain magnetic resonance (MR) imaging.Materials and Methods: We retrospectively reviewed cranial MR images of 1,241 patients who underwent contrast-enhanced brain imaging between January 1, 2008 and March 31, 2011, excluded images of inadequate quality of 130 patients, and ultimately analyzed images of 1,111 patients (544 male, 567 female). We assessed location, shape, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“… 3 Nakajima et al also proposed that RSLVN may be a precursor to or variant of subependymoma because of the similar radiological and clinical findings. 2 Multiple RSLVNs also will not inconsistent with subependymoma, because a case of multiple subependymoma was reported previously. 3 However, a definitive conclusion has been difficult because subependymoma has not been described as having a ring-shaped appearance.…”
Section: Case Reportmentioning
confidence: 93%
See 1 more Smart Citation
“… 3 Nakajima et al also proposed that RSLVN may be a precursor to or variant of subependymoma because of the similar radiological and clinical findings. 2 Multiple RSLVNs also will not inconsistent with subependymoma, because a case of multiple subependymoma was reported previously. 3 However, a definitive conclusion has been difficult because subependymoma has not been described as having a ring-shaped appearance.…”
Section: Case Reportmentioning
confidence: 93%
“…Subsequently, Nakajima et al reported a 0.45% prevalence of RSLVNs. 2 Although they noted RSLVNs might be benign lesions without rapid growth, histopathological confirmation has not been described. We report a case of RSLVN with histopathological examination of surgical specimens.…”
Section: Case Reportmentioning
confidence: 97%